2016
DOI: 10.1016/j.pmrj.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Effectiveness of Inpatient Rehabilitation After Heart Transplantation

Abstract: An inpatient rehabilitation program appears to positively impact optimal outcomes (functional recovery and discharge to home) for selected patients with HT and is comparable with regional and national FIM gain and efficiency for patients admitted to IRFs with other cardiac conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Like the group 14 cations, there is a decrease in aromaticity down the group from the moderately aromatic phosphorenylium cation (ASE = +16.4 kcal mol À1 ) to the weakly aromatic C 2 H 2 As + (+7.5 kcal mol À1 ) and C 2 H 2 Sb + (+3.7 kcal mol À1 ) cations. The value determined here for the aromatic stabilization of the phosphorenylium ion is significantly less than those calculated previously by homodesmotic reactions [Eisfeld and Regitz: 38.4 kcal mol À1 at G2; Gupta and Bansal: 28.9 kcal mol À1 at B3LYP/6-31 + G(d)], [49,50] due to common problems in such determinations including inconsistent ring strain and failure to balance the number of hyperconjugative interactions (Schemes 1 and 2). [13][14][15] Nevertheless, the C 2 H 2 P + cation is calculated to F I G U R E 1 Monoheterocyclic three-membered rings investigated for aromatic or antiaromatic properties T A B L E 3 Calculated NBO-ASE (kcal mol À1 , at M06-2X/ def2-TZVP) and NICS(0) π,zz (ppm, at M06-L/def2-TZVP) for planar three-membered rings C 2 H 2 X (X = CH + , SiH + , GeH + , SnH + , P + , As + , Sb + , Cl + , Br + , I + , S, Se, or Te)…”
Section: Aromaticity In Monoheterocyclic Three-membered Ringscontrasting
confidence: 64%
See 1 more Smart Citation
“…Like the group 14 cations, there is a decrease in aromaticity down the group from the moderately aromatic phosphorenylium cation (ASE = +16.4 kcal mol À1 ) to the weakly aromatic C 2 H 2 As + (+7.5 kcal mol À1 ) and C 2 H 2 Sb + (+3.7 kcal mol À1 ) cations. The value determined here for the aromatic stabilization of the phosphorenylium ion is significantly less than those calculated previously by homodesmotic reactions [Eisfeld and Regitz: 38.4 kcal mol À1 at G2; Gupta and Bansal: 28.9 kcal mol À1 at B3LYP/6-31 + G(d)], [49,50] due to common problems in such determinations including inconsistent ring strain and failure to balance the number of hyperconjugative interactions (Schemes 1 and 2). [13][14][15] Nevertheless, the C 2 H 2 P + cation is calculated to F I G U R E 1 Monoheterocyclic three-membered rings investigated for aromatic or antiaromatic properties T A B L E 3 Calculated NBO-ASE (kcal mol À1 , at M06-2X/ def2-TZVP) and NICS(0) π,zz (ppm, at M06-L/def2-TZVP) for planar three-membered rings C 2 H 2 X (X = CH + , SiH + , GeH + , SnH + , P + , As + , Sb + , Cl + , Br + , I + , S, Se, or Te)…”
Section: Aromaticity In Monoheterocyclic Three-membered Ringscontrasting
confidence: 64%
“…In the fluorinated thiirenium ion C 2 H 2 SF + , the acceptor ability of the σ S-F * orbital is counteracted by the donor S C H E M E 1 ASEs from homodesmotic reaction equations by Eisfeld and Regitz (phosphorenylium ion) and Glukhovstev, Laiter, and Pross (cyclopropenylium cation) (negative ASEs indicate aromaticity) calculated at G2 (in kcal mol À1 ) [49,51] S C H E M E 2 ASEs from homodesmotic reaction equations by Gupta and Bansal (negative ASEs indicate aromaticity) calculated at B3LYP/6-31 + G(d) (in kcal mol À1 ) [50] F I G U R E 2 Orbital illustration of pseudo 2π hyperconjugative aromaticity with electron withdrawing (EW) substituents and pseudo 4π hyperconjugative antiaromaticity with electron donating (ED) substituents in 3MR T A B L E 4 Calculated NBO-ASE (kcal mol À1 , at M06-2X/ def2-TZVP) for monosubstituted three-membered rings C 2 H 2 XR (X = S + , Se + , Te ability of the n s lone pair leading to an overall nonaromatic species (ASE = +1.5 kcal mol À1 ). However, moving to R = H (À7.5 kcal mol À1 ) or SiH 3 (À14.8 kcal mol À1 ) significantly increases the antiaromatic nature of the compound as there is destabilizing repulsion between the π C=C orbital and the n s lone pair in addition to the electron rich S-H or S-SiH 3 σ bond.…”
Section: Compoundmentioning
confidence: 99%
“…Many studies showed that the positive effects of physical rehabilitation in patients with chronic HF was confirmed [23][24][25]. Any phases of rehabilitation were effective to significantly increase the physical score, functional independence measure score, quality of life, and oxygen uptake in cardiopulmonary exercise tests [23][24][25][26]. Further efforts should be dedicated to preventing a decline in ADL at admission due to HF.…”
Section: [ ( F I G _ 2 ) T D $ F I G ]mentioning
confidence: 99%
“…They observed functional gains postrehabilitation, but improvements were more modest, required longer lengths of stay, and were associated with higher complication rates among transplant patients compared to general rehabilitation patients . Later work by Gupta et al in a small cohort of exclusively heart transplant recipients supported earlier findings that inpatient rehabilitation can lead to functional benefits after transplantation …”
Section: Introductionmentioning
confidence: 80%
“…16 Later work by Gupta et al in a small cohort of exclusively heart transplant recipients supported earlier findings that inpatient rehabilitation can lead to functional benefits after transplantation. 17 The present study aimed to extend on the work of Bowman et al by conducting an updated review of inpatient rehabilitation outcomes following cardiopulmonary transplantation, at the largest Heart and Lung Transplant center in Australia and New Zealand, from 2009 to 2016.…”
Section: Introductionmentioning
confidence: 99%